Newtonian Heating Effect on Heat Absorbing Unsteady MHD Radiating and Chemically Reacting Free Convection Flow Past an Oscillating Vertical Porous Plate - B. Prabhakar Reddy; O. D. Makinde (International Journal of Applied Mechanics and Engineering, 2022)
In this article, we have discussed in detail the effect of Newtonian heating on MHD unsteady free convection boundary layer flow past an oscillating vertical porous plate embedded in a porous medium with thermal radiation, chemical reaction and heat absorption. The governing PDEs of the model together with related initial and boundary conditions have been solved numerically by the finite element method. The dimensionless velocity, temperature and concentration profiles are analyzed graphically due to the effects of key parameters in the concerned model problem. Computed results for the skin friction coefficient, Nusselt number and Sherwood number are put in tabular form. It is observed that the thermal and mass buoyancy effects support the velocity whilst a reverse effect is noticed when the strength of the magnetic field is increased. The velocity and temperature enhances with an increase in the Newtonian heating and thermal radiation whilst a reverse effect is observed with an increase in the Prandtl number and heat absorption parameter. Increasing Schmidt number and chemical reaction parameter tends to depreciate both velocity and concentration. The Newtonian heating, thermal radiation and magnetic field tends to decrease in the skin friction. The Nusselt number increases with increasing Newtonian heating and heat absorption parameters. An increase in the Schmidt number and chemical reaction rate tends to improve the Sherwood number.